2017
DOI: 10.20944/preprints201711.0124.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NN-Harmonic Mean Aggregation Operators Based MCGDM Strategy in Neutrosophic Number Environment

Abstract: Abstract:The concept of neutrosophic number is a significant mathematical tool to deal with real 16 scientific problems because it can tackle indeterminate and incomplete information which exists 17 generally in real problems. In this article, we use neutrosophic numbers (a + bI), where a and bI 18 denote determinate component and indeterminate component respectively. We explore the 19 situations in which the input information is needed to express in terms of neutrosophic numbers. 20We define score functions a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Wang et al [51] explored the dual BM aggregation operator for SVNNs further. Harmonic mean AOs for SVNNs were presented by Mondal et al [52]. Ji et al [53] demonstrated the Frank prioritized BM in an SVN environment by their application in third-party logistics selection.…”
Section: Mamps Methodsmentioning
confidence: 99%
“…Wang et al [51] explored the dual BM aggregation operator for SVNNs further. Harmonic mean AOs for SVNNs were presented by Mondal et al [52]. Ji et al [53] demonstrated the Frank prioritized BM in an SVN environment by their application in third-party logistics selection.…”
Section: Mamps Methodsmentioning
confidence: 99%
“…NN consists of a crisp parameter and a value with a literal indeterminacy parameter (I), and can meritoriously explain the restricted confident and restricted indeterminate information as A 5 p þ qI for indeterminacy I ∈ [I À , I þ ] and A, p ∈ R (all real numbers). NN is also applied in various problems (Smarandache, 2015;Ye and Cui, 2018b;Ye, 2018;Mondal et al, 2021). Nevertheless, as far as we know, the model of Jaberi Hafshjani et al (2021) is the only study devoted to the DEA and NN.…”
Section: Neutrosophic Data Envelopment Analysismentioning
confidence: 99%
“…Wu, Wang, Peng, and Chen () developed prioritized aggregation operator for SVNNs considering the priorities of corresponding attributes by priority weights. Mondal, Pramanik, Giri, and Smarandache () presented Harmonic mean aggregation operator for SVNNs with the same consideration as in Wu et al Moreover, two or more functions are combined for adopting their advantages. The prioritized aggregation operators and Muirhead mean are combined by Garg and Nancy (a).…”
Section: Introductionmentioning
confidence: 99%